Interferon Lambda Genetics and Biology in Regulation of Viral Control - Hemann, Emily A.; Gale, Michael; Savan, Ram (Frontiers in Immunology, 2017)
Type III interferons, also known as interferon lambdas (IFNλs), are the most recent addition to the IFN family following their discovery in 2003. Initially, IFNλ was demonstrated to induce expression of interferon stimulated genes (ISGs) and exert antiviral properties in a similar manner to type I IFNs. However, while IFNλ has been described to have largely overlapping expression and function with type I IFNs, it has become increasingly clear that type III IFNs also have distinct functions from type I IFNs. In contrast to type I IFNs, whose receptor is ubiquitously expressed, type III IFNs signal and function largely at barrier epithelial surfaces, such as the respiratory and gastrointestinal tracts, as well as the blood brain barrier. In further support of unique functions for type III IFNs, single nucleotide polymorphisms (SNPs) in IFNL genes in humans are strongly associated with outcomes to viral infection. These biological linkages have also been more directly supported by studies in mice highlighting roles of IFNλ in promoting antiviral immune responses. In this review we discuss the current understanding of type III IFNs, and how their functions are similar to, and different from, type I IFN in various immune cell subtypes and viral infections.